(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article states that Zahiriddin Muhammad Babur is a person who not only possesses such human qualities as enlightenment, patriotism, humanity, sincerity, and generosity, but also serves as a true Muslim, especially in his work to know and fulfill the duties of Islam, conditions and its importance in strengthening the faith of Muslims.